Momentum spectra of electrons rescattered from rare-gas targets following their extraction by one- and two-color femtosecond laser pulses - Ray, D.; Chen, Zhangjin; De, S.; Cao, W.; Litvinyuk, I. V.; Le, A. T.; Lin, C. D.; Kling, M. F.; Cocke, C. L. (My University, 2011)
We have used velocity-map imaging to measure the three-dimensional momenta of electrons rescattered from Xe and Ar following the liberation of the electrons from these atoms by 45 fs, 800 nm intense laser pulses. Strong structure in the rescattering region is observed in both angle and energy, and is interpreted in terms of quantitative rescattering (QRS) theory. Momentum images have also been taken with two-color (800 nm + 400 nm) pulses on Xe targets. A strong dependence of the spectra on the relative phase of the two colors is observed in the rescattering region. Interpretation of the phase dependence using both QRS theory and a full solution to the time-dependent Schrödinger equation shows that the rescattered electrons provide a much more robust method for determining the relative phase of the two colors than do the direct electrons.